Proposing a comprehensive legal framework of special education for children with disabilities in Malaysia / Muhammad Fikri Othman - Othman, Muhammad Fikri (2023)
Education is essential to everyone, including children with disabilities. Education plays a vital role in their life since it will ensure their future, enable them to make decisions and allow them to fully participate in society. Even though the government has provided the right to education to every citizen, however, the educational rights of children with disabilities are not fully protected. There are problems with the current laws and regulations regarding the special education of children with disabilities in Malaysia, such as scattered and loopholes in the laws. For example, there are a few provisions that are very general in nature which are relating to special education law namely Article 8 and Article 12 of the Federal Constitution, Section 28 of the Persons with Disabilities Act 2008, Section 40 and Section 41 of the Education Act 1996, and the Education (Special Education) Regulations 2013. The objectives of this research are to examine the factors that contribute to the insufficiency of the laws relating to special education for children with disabilities in Malaysia, to analyse the practice of the laws relating to special education for children with disabilities in the United Kingdom, Singapore and Thailand, and to propose a comprehensive legal framework of special education for children with disabilities in Malaysia. This research is based on doctrinal analysis or library-based research through primary and secondary sources of law such as the Federal Constitution of Malaysia, the Persons with Disabilities Act 2008, the Education Act 1996, the Education (Special Education) Regulations 2013, case law, textbooks, and journals. Besides, this research is based on the data from semi-structured interviews conducted with selected special education teachers, welfare department officers from the Ministry of Women, Family and Community Development, relevant officers from the Ministry of Education, university experts in disability study and human rights, and parents of children with disabilities. In addition, observation has been conducted on four schools in Klang Valley to examine the teaching activities, diagnostic procedures, and school facilities. The research suggested that the current laws and regulations relating to special education for children with disabilities are insufficient in protecting their educational rights, hence directly affecting the special education sector in Malaysia. Besides, the research also suggested that there is a need for the government to enact a specific Act relating to special education for children with disabilities in Malaysia to fully protect their educational rights. It is hoped that the research can contribute to the improvement in protecting the educational rights of children with disabilities through the proposed comprehensive legal framework of special education for children with disabilities in Malaysia.